REVERSAL OF METABOLIC SYNDROME WITH PLANT BASED DIET AND EXERCISE - Pramod Tripathi; Mamata Hiremath; Anagha Vyawahare (AYUSHDHARA, 2020)
This study aimed to investigate the effectiveness of a specified diet pattern and exercise like lymphatic and strength-building exercises (FFD protocol) to enhance weight and fat loss. A 45-year-old male with a history of obesity and diabetes mellitus (DM) enrolled in the study. The patient followed a specified diet along with lymphatic and strength-building exercises. Follow up was done for 6 months where, baseline characteristics, anthropometric measurements and biochemical parameters were measured in visit 1 and visit 2. The patient was off DM medication in 10 days. In first follow up (3 months) weight, BMI, waist circumference and body fat was significantly reduced. Whereas skeletal muscle mass was increased. A drop in HbA1C, fasting insulin, fasting blood sugar level and postprandial blood sugar levels were observed. In comparison to first follow up the second follow up after 6 months, shows substantial changes in the basal parameters. A drastic decline in HbA1c was reported from 6.1% to 5.5%. The FFD program comprehensively targets diabetes, ultimately clearing GTT the harbinger of the defeat of diabetes and visceral obesity, thereby successfully reversing the cluster of components of this morbid syndrome.